Sport, Mental Illness and Sociology - Atkinson, Michael (Research in the Sociology of Sport Ser., 2018)
This book approaches the study of mental illness in sport cultures from a variety of social scientific perspectives. Contributions focus on the multiple manifestations of mental illness within sport cultures, and the degree to which sport may be utilized as a means of helping people who struggle with mental illness.